Transformation of Cooperative Financial Governance Through Implementation of Cooperative Accounting Information System (SIKOP) Based on SAK EP in Blitar Regency - Achmad Murdiono; Fadia Zen; Subagyo Subagyo (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2025)
Cooperatives are one of the important pillars in the economic development of the community, especially in Blitar Regency. However, many cooperatives still face serious challenges in accountable and transparent financial governance. The low understanding of Private Entity Financial Accounting Standards (SAK EP) and the limited use of information technology are the main obstacles in preparing reliable financial reports. This community service activity aims to transform cooperative financial governance through the development and implementation of the Cooperative Accounting Information System (SIKOP) based on SAK EP. The approach used is Participatory Action Research (PAR), involving 30 production cooperatives in Blitar Regency as partners. The activities were carried out through the stages of identifying needs, developing systems, intensive training, and assisting in implementation and evaluation. The results of the activities showed a significant increase in the understanding and skills of cooperative administrators in preparing financial reports according to standards, as well as increasing the efficiency and accuracy of recording financial transactions. With the implementation of SIKOP, partner cooperatives also showed increased transparency and accountability which had an impact on member trust and potential access to funding. This program shows that digitizing SAK EP-based financial reports through SIKOP can be an effective solution in building professional, accountable, and sustainable cooperative governance.